Kinetic study and simulation of molybdenum borides for hydrogen evolution reaction - Harunal Rejan Ramji; Muhammad Qhaliff Zainal Ibidin; Nicolas Glandut; Joseph Absi; Lim Soh Fong (Institute of Advanced Engineering and Science, 2024)
This paper presented the kinetic study of molybdenum borides via the Volmer-Heyrovsky-Tafel (V-H-T) mechanistic steps for hydrogen evolution reaction (HER). A theoretical approach was carried out to investigate the kinetic properties of several molybdenum boride materials for HER in 0.5 M H2SO4. Our findings offer definitive proof that the simulated results show that B, Mo, Mo2B, and α-MoB, proceed through V-H mechanistic steps (slower kinetics) while β-MoB and MoB2 exhibit V-H-T mechanistic steps with higher kinetics. The kinetic parameters were determined in terms of the standard rate constant parameters for the Volmer step (kV, k-V), Heyrovsky step (kH, k-H), and rate constant for the Tafel step (kT, k-T). The simulation was able to predict the overpotential at 10 mA/cm2, η10 recorded at approximately 780, 585, 480, 350, 310, and 300 mV for B, Mo, Mo2B, α-MoB, β-MoB, and MoB2 respectively. Based on these findings, the adopted mathematical model shows good coherency to the experimental findings. The simulation work provides a good numerical estimation of the characteristics of the electrocatalyst for HER. This paper successfully elucidated the reaction mechanisms (V-H-T steps) and understood the rate-limiting steps involved in the HER process on Mo-B materials.